When London burned to sticks: The economic impact of the Great Fire of 1666 - Philipp Ager; Maja Uhre Pedersen; Paul Sharp; Xanthi Tsoukli (European Historical Economics Society (EHES), 2024)
This study provides a comprehensive understanding of the Great Fire's effects on London's economic geography. Our analysis reveals both continuity and change. There was a swift postfire recovery accompanied by some shift in economic activity towards the City of Westminster by 1690, with markets spreading outside the City, but financial services largely remaining inside. Analysis of London Hearth Tax records further illustrates a significant change in the wealth distribution, with wealthier households returning to fire-impacted areas, reshaping the city's housing and social structure.
Keywords: N23; N93; 330; Great Fire of London; Economic Geography; Location of economic activity